Explaining Prejudicial Attitudes and Bias-Motivated Aggression in Belgium: a Comparison of Individual-Level Theoretical Models - Pauwels, Lieven (European journal on criminal policy and research, 2024)
Prejudice and bias-motivated aggression (BMA) are pervasive social problems. Scholars have tested numerous competing theoretical models to demonstrate the key predicates of prejudice and BMA, including intergroup contact, dual process (i.e., right-wing authoritarianism and social dominance orientation), perceived injustice, peer socialization, and empathy. Yet, studies to date have not empirically examined the comparative strength of these theoretical perspectives to explain the correlates of (a) prejudice and (b) BMA. This study seeks to address this gap. Utilizing a sample of young 1,001 Belgian participants, this study explores the association between key constructs from different theoretical perspectives to better understand prejudice and BMA towards immigrant populations. Findings show that when accounting for all models of prejudice and BMA, the strongest predictors of prejudice emerge from the dual-process model, the empathy model (outgroup empathy), and the quality (not frequency) of intergroup contact. Yet, prejudice and exposure to peer outgroup hostility are the strongest predictors of BMA. We discuss the implications of our findings and suggest that drawing on criminological theories of prejudice and BMA can be integrated to provide a more nuanced understanding of the nature of prejudice and BMA than what is currently known. We conclude by highlighting some directions for future research on prejudice and BMA.